PENERAPAN MODEL AUDITORY, INTELLECTUAL , REPETITION (AIR) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KEANEKARAGAMAN HAYATI KELAS V SD IT MUHAMMADIYAH BIREUEN - Askal Azqia; Fatma Zuhra; Faizah M.Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' learning outcomes on the topic of biodiversity through the implementation of the Auditory, Intellectual, Repetition (AIR) learning model in fifth-grade at SD IT Muhammadiyah Bireuen. This research is a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection phases. The subjects of this study were 20 students. Data were collected through learning outcome tests, teacher and student activity observation sheets, and response questionnaires. The results of the study in Cycle I showed that teacher activity reached an average of 87.69% and student activity reached 82.09% (both in the excellent category), but classical learning completeness only reached 40% (8 out of 20 students) with a low average score. After improvements were made in Cycle II, a significant increase occurred in students' learning outcomes, with the classical completeness rate reaching 85% (17 out of 20 students). This indicates that the success indicator of 80% had been exceeded. Based on these results, it can be concluded that the implementation of the AIR learning model is effective in improving Science (IPA) learning outcomes on biodiversity materials for fifth-grade students at SD IT Muhammadiyah Bireuen.